Penggunaan Metode Inkuiri dalam Peningkatan Hasil Belajar Matematika di Kelas V Sekolah Dasar - Budiarti, Ani; Markamah, Markamah; Sutama, Sutama (Lembaga Yasin AlSys, 2022)
The Use of the Inquiry Method in Improving Mathematics Learning Outcomes in Grade V Elementary School. This study aims to explain the steps of the inquiry method in improving student achievement in mathematics in grade V elementary school. The research was conducted at SDN 2 Jagong in two cycles which in the end the increase in learning achievement reached 88.5% as expected by the teacher in this lesson. These results indicate that the application of the inquiry method is very appropriate in increasing learning achievement on the theme of building space. In learning mathematics that uses the inquiry method, the teacher uses stages, including forming groups so that students can and are able to work together to formulate problems in groups, solve problems in groups given by the teacher with responsibility. Furthermore, the teacher monitors or observes student activities in the implementation of learning. The application of this inquiry method emphasizes the activeness, attention, and ability of students in answering questions given. by the teacher. Keywords: Inquiry method, learning outcomes, mathematics